1994
DOI: 10.7556/jaoa.1994.94.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Telangiectasia macularis eruptiva perstans

Abstract: Telangiectasia macularis eruptiva perstans MONIQUE s. COHN, DO MICHAEL J. MAHON, DO Telangiectasia macularis eruptiva perstans (TMEP) is a rare form of mastocytosis. It appears most frequently in adults and only occasionally will affect young children or infants. In this disease, multiple brownish-red confluent macules and telangiectasias develop, primarily on the trunk. Pruritus frequently occurs, and may be mild to severe. Most patients have only skin involvement; however, involvement may be systemic as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…The mastocytosis syndrome is known to appear slightly more often in men than in women (1.5:1) 11 . Our review of the literature on TMEP cases reported since 1990, in contrast, revealed reports on 15 men and 14 women, 2,4,8–10,12–29 not including our report. The equal prevalence of TMEP among men and women differs from the slightly greater prevalence among men of the mastocytosis group to which TMEP belongs.…”
contrasting
confidence: 55%
“…The mastocytosis syndrome is known to appear slightly more often in men than in women (1.5:1) 11 . Our review of the literature on TMEP cases reported since 1990, in contrast, revealed reports on 15 men and 14 women, 2,4,8–10,12–29 not including our report. The equal prevalence of TMEP among men and women differs from the slightly greater prevalence among men of the mastocytosis group to which TMEP belongs.…”
contrasting
confidence: 55%
“…Although UP is generally well‐recognized when presenting with its classical appearance, unusual macroscopic presentations of cutaneous mastocytosis are often misdiagnosed given the potential variability in clinical presentation and subtlety with establishing the histological diagnosis in the context of a low pre‐test probability 14 . Adult patients with UP often have a high likelihood of an underlying systemic mast cell disorder 15 . One case series described systemic involvement in up to 47% of cases with cutaneous mastocytosis 16 with aggressive (non‐indolent) systemic mastocytosis in up to 9% of those cases.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Adult patients with UP often have a high likelihood of an underlying systemic mast cell disorder. 15 One case series described systemic involvement in up to 47% of cases with cutaneous mastocytosis 16 with aggressive (non‐indolent) systemic mastocytosis in up to 9% of those cases. Therefore, any patient presenting with characteristic skin findings should be investigated as having a cutaneous manifestation of systemic mastocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…TMEP is a rare manifestation of cutaneous mastocytosis and is often overlooked or misdiagnosed given its variable clinical presentation [15] and subtlety with establishing the histological diagnosis [16]. Unlike other forms of cutaneous mastocytosis, patients with TMEP have a high likelihood of an underlying systemic mast cell disorder [17,18]. One case series described systemic involvement in up to 47% of cases with TMEP [6] with aggressive (non-indolent) systemic mastocytosis in up to 9% of those cases.…”
Section: Discussionmentioning
confidence: 99%